Frequency tuning and intensity coding of sound in the auditory periphery of the lake sturgeon, Acipenser fulvescens - Meyer, Michaela (Company of Biologists, 2010)
Acipenser fulvescens, the lake sturgeon, belongs to one of the few extant non-teleost ray-finned (bony) fishes. The sturgeons (family Acipenseridae) have a phylogenetic history that dates back about 250 million years. The study reported here is the first investigation of peripheral coding strategies for spectral analysis in the auditory system in a non-teleost bony fish. We used a shaker system to simulate the particle motion component of sound during electrophysiological recordings of isolated single units from the eighth nerve innervating the saccule and lagena. Background activity and response characteristics of saccular and lagenar afferents (such as thresholds, response–level functions and temporal firing) resembled the ones found in teleosts. The distribution of best frequencies also resembled data in teleosts (except for Carassius auratus, goldfish) tested with the same stimulation method. The saccule and lagena in A. fulvescens contain otoconia, in contrast to the solid otoliths found in teleosts, however, this difference in otolith structure did not appear to affect threshold, frequency tuning, intensity- or temporal responses of auditory afferents. In general, the physiological characteristics common to A. fulvescens, teleosts and land vertebrates reflect important functions of the auditory system that may have been conserved throughout the evolution of vertebrates.